Bukan Sekedar Pelipur Lara: Promosi Pariwisata dalam Dongeng “Nusantara Bertutur” Koran Kompas 2019 - I Nyoman Darma Putra; Eva Lailatur Riska (Mudra Jurnal Seni Budaya, 2022)
Literature and tourism have long had a close relationship, but researchers of the fields have paid little attention on them. This study aims to examine aspects of the tourism narrative in the Nusantara Bertutur(Fairy Tales of the Archipelago) published by Kompason its Sunday edition throughout the year of 2019. The data were selected purposively from all fairy tales published every Sunday. Of the 49 fairy tales published, 25 of them contain narratives about travelling, tourist attractions or activities. The data were analyzed with a tourism literary approach with an emphasis on the theme, setting, and tourism aspects narrated in fairy tales. The results of the study show that the fairy tales of Nusantara Bertutur are more than just entertainment, because they also contain paintings of natural beauty (sunrise, beautiful lakes, beaches, underwater nature, and rural nature); various kinds of Indonesian cuisine; and narratives about the traditions or rituals of the archipelago such as the Kasada Ceremony and Karo Holiday in Bromo (East Java), the Sigale-gale carnival on Lake Toba, and Jathilan in Magelang, Central Java. This article offers a new understanding that fairy tales are not only full of stories with ethical and moral messages or solace but also contain the promotion of tourist attractions and the introduction of various traditions and cultures of the archipelago to children.